(untitled) (BIMRAD Journal, 2025)
The Sino-Indian competition is not a recent development when it comes to global and regional affairs. In recent years, the crisis between China and India has manifested serious geostrategic risks to the stability and safety of the South Asian region and maritime domain. This paper precisely analyses the Sino Indian maritime competition in the Indian Ocean where both the Asian powers are regarded as one of the most significant naval capabilities for their geostrategic vision. An overview of China’s and India’s strategic objectives in the Indian Ocean Region (IOR) is what this study aims to convey in the first section. The section analyzes the geo political and geo-economic importance of Indian Ocean for both China and India. The latter section sheds light on China’s growing concern for the IOR stemmed from its Sea Lines of Communications (SLOCs) security and explains the expanding activities of China in the region. The Indian security community views China’s continued modernization of its military, increased power projection in the Indian Ocean, and political and economic ties with the IOR states as measures to counterbalance India’s dominance in the region. The next section outlines how China’s increasing sway in the IOR is becoming a major worry for New Delhi. In an effort to project power and protect its strategic interests both inside and outside the IOR, India has worked to modernize and bolster its armed forces over the past ten years, particularly the navy. India is currently envisioning a more grandiose and newer role for itself in the IOR by procuring infrastructure in a number of IOR countries. India has been trying to thwart China’s attempts to establish IOR dominance. This, combined with India’s essential naval build-up and overwhelming spatial advantage, would significantly challenge China’s goal of enhancing its leverage in the IOR through its “String of Pearls.” Thus, all these counter activities of the two Asian powers against each other have gradually been fueling the maritime competition in the IOR a more intense one. BIMRAD Journal VOLUME 5, ISSUE 1, DEC 2024; PP-63-84